The burden of neurothrombectomy call: a multicenter prospective study. (20th April 2018) - Williams, Michelle M; Wilson, Taylor A; Leslie-Mazwi, Thabele; Hirsch, Joshua A; Kellogg, Ryan T; Spiotta, Alejandro M; De Leacy, Reade; Mocco, J; Albuquerque, Felipe C; Ducruet, Andrew F; Arthur, Adam; Srinivasan, Visish M; et al.
Abstract : Introduction: Neurothrombectomy frequency is increasing, and a better understanding of the neurothrombectomy call burden is needed. Methods: Neurointerventional physicians at nine participating stroke centers prospectively recorded time requirements for all neurothrombectomy (NT) consultations over 30 consecutive 24 hour call periods. Results: Data were collected from a total of 270 days of call. 214 NT consultations were reported (mean 0.79 per day), including 130 'false positive' consultations that ultimately did not lead to thrombectomy (mean 0.48 per day). 84 NT procedures were performed at the nine centers (0.32 per day, or 1 every 3 days). Most (59.8%) consultations occurred between 5pm and 7am. 30% of thrombectomy procedures resulted in delays in scheduled cases; treating physicians had to emergently travel to the hospital for 51.2% of these cases. A median of 27 min was spent on each false positive consultation and 171 min on each thrombectomy. Overall, the median physician time spent on NT responsibilities per 24 hour call period was 69 min (mean 85 min; IQR 16–135 min). Conclusions: NT consultations are frequent and often disrupt physician schedules, requiring physicians to commute in from home after hours in the majority of cases. As procedural and consultation volumes increase, it is crucial to understand the significant burden of call on neurointerventional physicians and develop strategies that reduce the potential for burnout. Importantly, this study was performed prior to the completion of the DAWN and DEFUSE3 trials; NT consultations are expected to continue to increase in the future.